2022
DOI: 10.1007/s41742-022-00448-z
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distribution of Phosphorous Fractions and Bioavailability of the Nutrient in the Southern Indian Ocean

Abstract: The study evaluated concentration, vertical distribution, and bioavailability of phosphorus fractions in the Indian Ocean core sediments. Sediment samples were collected from two sites in the Indian Ocean during January–February 2010 using gravity corer. Phosphorus fractions in sediments were analyzed by a modified sequential extraction procedure (SEDEX). The vertical profile revealed silt and clay as dominant grain size fractions in both cores. The enriched levels of organic carbon were observed in samples du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Previous studies (Yang et al 2019, Liao et al 2020) suggested that higher Ex-P values occur near river mouths and surface sediments. However, our selected core sample layers were slightly deeper (37 cm-42 cm, see figure 3), and contained Ex-P, which is easily available in the water column (Mullungal et al 2022). Thus, the low values of Ex-P can be attributed to the fact that they represent the residues remaining following their utilization by primary producers.…”
Section: Impact Of Riverine Tp Loading On P Species In the Sedimentmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies (Yang et al 2019, Liao et al 2020) suggested that higher Ex-P values occur near river mouths and surface sediments. However, our selected core sample layers were slightly deeper (37 cm-42 cm, see figure 3), and contained Ex-P, which is easily available in the water column (Mullungal et al 2022). Thus, the low values of Ex-P can be attributed to the fact that they represent the residues remaining following their utilization by primary producers.…”
Section: Impact Of Riverine Tp Loading On P Species In the Sedimentmentioning
confidence: 97%
“…The SEDEX method extracts different P species from sediment based on their solubility and reactivity. A sequential extraction procedure was applied to estimate five species of P from sediment: (1) Exchangeable P (Ex-P) or loosely bound P, an important inorganic P species, is absorbed by sediment, can easily be released into the water column, and is used by phytoplankton (Mullungal et al 2022). ( 2) Iron-bound P (Fe-P), an inorganic P species, is produced by co-precipitation with Fe/Mn oxides or hydroxides (Zhou et al 2016).…”
Section: Sequential Extraction Of Pmentioning
confidence: 99%